Gambaran Pengetahuan Masyarakat Pekalongan Tentang Covid-19 - Izzatun Nidaa (JURNAL LITBANG KOTA PEKALONGAN, 2020)
In early 2020, the world community was shocked by the emergence of Coronavirus Disease 2019 (Covid-19). Common signs and symptoms of Covid-19 infection include acute respiratory symptoms such as fever, cough and shortness of breath. Until now, a vaccine has not been found to prevent Covid-19, so prevention efforts are the first steps that can be taken to prevent the spread of Covid-19 infection. This study aims to obtain an overview of the Pekalongan community's knowledge about Covid-19 and describe an overview of public opinions regarding health promotion about Covid-19 carried out by the Primary Health Care (puskesmas). This research uses descriptive quantitative research methods with cross sectional design. The data collection method uses an online questionnaire via Google Form. Data collection was carried out on 7-10 June 2020. From the results of the study, it was found that most respondents (72%) had a good level of knowledge about Covid-19. Most of them (70%) received information about Covid-19 from online media, and 27% from TV. Most respondents (60%) have never received information about Covid-19 from the nearest puskesmas. Most of the respondents felt the need (32%) and very need (61%) for education about Covid-19 from the puskesmas. Most of the respondents (77%) expect the health promotion about Covid-19 from the puskesmas through health education by puskesmas officers. For the health sector, especially the Health Office (Dinas Kesehatan) through the local puskesmas, it is hoped that there will be health promotion activities about Covid-19 to the community through health education by puskesmas officers. Keywords: Knowledge, virus, Covid-19, pandemic